2012
DOI: 10.4161/fly.22108
|View full text |Cite
|
Sign up to set email alerts
|

Drosophila Protein interaction Map (DPiM)

Abstract: Proteins perform essential cellular functions as part of protein complexes, often in conjunction with RNA, DNA, metabolites and other small molecules. The genome encodes thousands of proteins but not all of them are expressed in every cell type; and expressed proteins are not active at all times. Such diversity of protein expression and function accounts for the level of biological intricacy seen in nature. Defining protein-protein interactions in protein complexes, and establishing the when, what and where of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 40 publications
1
13
0
Order By: Relevance
“…Alternatively, we cannot exclude that Akirin and the SWI/SNF complex are recruited on the promoter of Relish target genes independently of Relish itself. Consistent with this SWI/SNF-dependent chromatin remodeling process, it was recently suggested that DNA-methyltransferase associated protein 1 (DMAP1), also known to interact with BAP55 (Guruharsha et al , 2012 ), would associate with Akirin (Goto et al , 2014 ). The possibility that methyl groups on H3K4 are replaced by acetyl groups to allow full transcription would fit with our finding that H3K4ac is a hallmark of active Akirin-dependent promoters.…”
Section: Discussionmentioning
confidence: 90%
“…Alternatively, we cannot exclude that Akirin and the SWI/SNF complex are recruited on the promoter of Relish target genes independently of Relish itself. Consistent with this SWI/SNF-dependent chromatin remodeling process, it was recently suggested that DNA-methyltransferase associated protein 1 (DMAP1), also known to interact with BAP55 (Guruharsha et al , 2012 ), would associate with Akirin (Goto et al , 2014 ). The possibility that methyl groups on H3K4 are replaced by acetyl groups to allow full transcription would fit with our finding that H3K4ac is a hallmark of active Akirin-dependent promoters.…”
Section: Discussionmentioning
confidence: 90%
“…H2A.Z chaperone activity seems to be specific for ANP32E since the H2A.Z interaction maps to a discrete conserved sequence within the LCAR of ANP32E that is not found in ANP32A or ANP32B 29 , 56 . Intriguingly, however, the Drosophila Protein Interaction Map identified variant H2A (Dmel\His2Av), the precursor of mammalian H2A.Z, as a Mapmodulin-interacting factor 60 . This suggests a conserved role for ANP32 proteins in regulating H2A.Z placement.…”
Section: Anp32 Proteins Regulate Chromatin By Various Meansmentioning
confidence: 99%
“…The Mediator complex that regulates transcription (Allen and Taatjes 2015) and the BRD4 BET domain protein that binds acetylated histones (Hsu and Blobel 2017) are candidates for such factors. Mammalian Mediator interacts with NIPBL (Nipped-B) (Kagey et al 2010) and an affinity chromatography-mass spectrometry screen revealed that the Drosophila MED30 Mediator subunit interacts with Nipped-B (Guruharsha et al 2012). It was recently reported that human BRD4 interacts with NIPBL and that BRD4 mutations cause birth defects similar to those caused by NIPBL mutations (Olley et al 2018).…”
Section: The Med30 Mediator Subunit and The Fs(1)h Bet Domain Proteinmentioning
confidence: 99%